2012
DOI: 10.1007/s00343-012-1239-z
|View full text |Cite
|
Sign up to set email alerts
|

Pigment characterization for the 2011 bloom in Qinhuangdao implicated “brown tide” events in China

Abstract: A large-scale bloom occurred from May to June in 2011 in sea area near Qinhuangdao of the Bohai Sea, leading to huge damage of the scallop culture industry. Similar blooms have been observed in this region for three years. The causative species of the bloom, which dominated the phytoplankton community with the maximum cell density around 10 9 cell/L, could not be identifi ed with morphological features due to the small cell size (~2 m m). A pigment analytical method was then adopted to analyze the pigment prof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 52 publications
(25 citation statements)
references
References 41 publications
1
24
0
Order By: Relevance
“…Picosized Chl a (<2 mm) was about 80% of the total Chl a content, and nano-sized Chl a (2-20 mm) was about 20%, while micro-sized Chl a (>20 mm) was less than 1%. But-fuco, Fuco, Diad and Chl a were the major pigment components in the pico-sized and nano-sized phytoplankton samples (Kong et al, 2012). Station Q3 (119824.660 0 E, 39846.924 0 N), which was outside the bloom area, was located at the Yanghekou Harbor and approximately 4 km away from stations Q1 (Kong et al, 2012).…”
Section: Background Of the Sampling Sitesmentioning
confidence: 99%
See 1 more Smart Citation
“…Picosized Chl a (<2 mm) was about 80% of the total Chl a content, and nano-sized Chl a (2-20 mm) was about 20%, while micro-sized Chl a (>20 mm) was less than 1%. But-fuco, Fuco, Diad and Chl a were the major pigment components in the pico-sized and nano-sized phytoplankton samples (Kong et al, 2012). Station Q3 (119824.660 0 E, 39846.924 0 N), which was outside the bloom area, was located at the Yanghekou Harbor and approximately 4 km away from stations Q1 (Kong et al, 2012).…”
Section: Background Of the Sampling Sitesmentioning
confidence: 99%
“…Large-scale blooms occurred again in 2011, although the impacts of this bloom are currently unknown. In a previous study (Kong et al, 2012), we reported that the major pigments detected from the bloom were 19 0 -butanoyloxyfucoxanthin (But-fuco), fucoxanthin (Fuco), diadinoxanthin (Diad) and Chlorophyll a (Chl a), and high content of But-fuco was the most significant characteristics of the causative species of the bloom. Based on the pigment composition and content, the causative species could be tentatively identified as a pelagophyte, haptophyte or silicoflagellate (Edvardsen et al, 2007;Zapata et al, 2004).…”
mentioning
confidence: 99%
“…anophagefferens is a newly documented brown tide algae species in China . Next to America and South Africa, and China is the third-largest regional that suffers from brown tide (Kong et al 2012). However, brown tides in China have been rarely investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Large-scale brown tide blooms caused by A. anophagefferens occurred in the coastal waters of Qinhuangdao, China from 2009 to 2014 (State Oceanic Administration People's Republic of China 2009;. In particular, the largest scale of all was that in 2010, where 3350 km2 sea surface was affected (State Oceanic Administration People's Republic of China 2010) and Argopecten irradians mariculture was devastated (Kong et al 2012; with an estimated economic loss of 0.2 billion RMB (State Oceanic Administration People's Republic of China 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation